2020
DOI: 10.1371/journal.pone.0243530
|View full text |Cite
|
Sign up to set email alerts
|

Food reward sensitivity, impulsivity, and weight change during and after a 3-month weight loss program

Abstract: Background Greater sensitivity to food rewards and higher levels of impulsivity (and an interaction between these variables, termed “reinforcement pathology”) have been associated with obesity in cross-sectional studies. Less is known regarding how these constructs may impact attempts at weight loss or longer-term weight loss maintenance. Methods We provided 75 adults (69%Female, 84%White, age = 50.8y, BMI = 31.2kg/m2) with a 3-month Internet-based weight loss program and assessed weight, food reward sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…A much larger study ( n = 111) by O'Neil et al [ 32 ] found that a 4% weight loss induced by a 12‐week commercial weight loss program, consisting of caloric restriction, encouragement of physical activity, and regular meetings, led to decreases in hedonic hunger. Similarly, a study by Ross et al [ 33 ] reported that a 3‐month behavioral weight loss program resulted in reduced food reward sensitivity and impulsivity after an average 6‐kg (7%) weight loss. The two latter studies measured hedonic hunger with the PFS, and as such, results are similar and comparable with ours.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A much larger study ( n = 111) by O'Neil et al [ 32 ] found that a 4% weight loss induced by a 12‐week commercial weight loss program, consisting of caloric restriction, encouragement of physical activity, and regular meetings, led to decreases in hedonic hunger. Similarly, a study by Ross et al [ 33 ] reported that a 3‐month behavioral weight loss program resulted in reduced food reward sensitivity and impulsivity after an average 6‐kg (7%) weight loss. The two latter studies measured hedonic hunger with the PFS, and as such, results are similar and comparable with ours.…”
Section: Discussionmentioning
confidence: 91%
“…Ross et al [ 33 ] reported that a greater food reward sensitivity (from PFS) was associated with greater body weight but not with weight loss. Contrarily, O'Neil and colleagues [ 32 ] showed that a decrease in the aggregated PFS score was associated with a greater percentage of weight loss and with improvements in reported weight control behaviors determined by the Eating Behavior Inventory.…”
Section: Discussionmentioning
confidence: 99%
“…First, there may be a learning effect where people improve with repeated testing, as people improved from 0 to 12 weeks, with further significant improvement from 12 to 24 weeks. Second, BWL can improve DD without any training in EFT (Ross et al, 2020 ). BWL may include treatment components that foster a more prospective mindset, leading to reductions in DD.…”
Section: Discussionmentioning
confidence: 99%
“…This research is in line with the previous study which showed that individuals who are higher in Sensitivity of Reward (SR) have a greater risk of being overweight because they feel a very large desire for food because of the activation of these desires that come from the brain's response and are encouraged to realize the desire for food as a reward (16). In other studies conducted in adults, greater sensitivity and impulsive levels to food gifts were associated with food purchases that were high in FSS and related to obesity (17).…”
Section: Discussionmentioning
confidence: 96%